Quantification of the effect of body mass index on cricothyroid membrane depth: a cross-sectional analysis of clinical CT images. Issue 5 (24th February 2021) - Ghaffar, Sadia; Blankenstein, Tom Nicholas; Patel, Dilip; Theodosiou, Catherine; Griffith, David
Abstract : Objectives: The recommended front of neck access procedure in can't intubate, can't oxygenate scenarios relies on palpation of the cricothyroid membrane (CTM), or dissection of the neck down to the larynx if CTM is impalpable. CTM palpation is particularly challenging in obese patients, most likely due to an increased distance between the skin and the CTM (CTM depth). The aims of this study were to measure the CTM depth in a representative clinical sample, and to quantify the relationship between body mass index (BMI) and CTM depth. Methods: This is a retrospective analysis of 355 clinical CT scans performed at a teaching hospital over an 8-month period. CTM depth was measured by two radiologists, and mean CTM depth calculated. Age, gender, height and weight were recorded, and BMI calculated. Linear relationships between patient characteristics and CTM depth were assessed in order to derive a predictive equation for calculating CTM depth. The variables included for this model were those with a strong association with CTM depth, that is, a p value of 0.10 or less. Results: Mean CTM depth was 8.12 mm (IQR 6.36–11.70). There was no association between CTM depth and sex (β −0.33, 95% CI −1.33 to 0.68, p=0.53), height (cm) (β 0.01, 95% CI −0.05 to 0.06, p=0.79) or age (years) (β −0.01, 95% CI 0.10 to 0.15, p=0.62). Increasing weight (kg) (β 0.12, 95% CI 0.10 to 0.15, p<0.001) and BMI (kg/m 3 ) (β 0.52, 95% CI 0.44 to 0.60, p<0.001) were strongly associated with CTM depth. Predicted CTM depth increased from 6.4 mm (95% CI 4.9 to 8.1) at a BMI of 20 kg/m 2 to 16.8 (95% CI 13.7 to 20.1) at BMI 40 kg/m 2 . Conclusion: CTM depth was strongly associated with BMI in a retrospective analysis of patients having clinical CT scans.